Anesthetic Management of a Child with Fraser Syndrome and an Atrial Septal Defect Undergoing Laparoscopic Orchidopexy: A Case Report - Purwoko; Bambang Novianto; Samsul Rizal (HM Publisher, 2026)
Introduction: Fraser syndrome is a rare autosomal recessive disorder with multisystem manifestations, including craniofacial, ocular, urogenital, and musculoskeletal anomalies, and it may create anesthetic challenges related to difficult airway management. The risk is magnified when congenital heart disease and laparoscopic surgery coexist, because each adds an independent physiologic burden to a child with limited reserve. Case presentation: A 10-year-old boy weighing 8.3 kg and measuring 80 cm, with Fraser syndrome, bilateral anophthalmia, intellectual disability, a history of congenital cytomegalovirus infection, and marasmic malnutrition, underwent laparoscopic exploration of the right testis and orchidopexy of the left testis. Echocardiography demonstrated an atrial septal defect with right atrial and right ventricular dilatation; the patient was classified as American Society of Anesthesiologists physical status III. After midazolam 1 mg premedication, anesthesia was induced with fentanyl 3 mcg/kg, sevoflurane 1-2 vol%, atracurium 5 mg, and dexamethasone 4 mg, and the trachea was intubated with a 4.5-mm cuffed tube. Anesthesia was maintained with sevoflurane 1.5-2 vol% and 50% oxygen. Over the 2-hour procedure, hemodynamics were stable (blood pressure 100-130/60-68 mmHg, heart rate 82-95 beats/min) with a net positive fluid balance of 10 mL. The patient was extubated and remained stable through 24 hours. Conclusion: Safe anesthesia in this setting rested on a layered airway plan, an understanding of shunt physiology, close hemodynamic monitoring, and measured ventilation and fluid strategies rather than on any single drug regimen. The report also highlights data elements that should be documented prospectively to strengthen comparability across similar cases.